TINJAUAN PERTANGGUNGJAWABAN PIDANA BAGI KORPORASI YANG MELAKUKAN INSIDER TRADING DALAM PASAR MODAL - Berinda Sylvia Raganatha (Refleksi Hukum: Jurnal Ilmu Hukum, 2017)
because it has many functions and benefits. Among its functions and benefits, there is a problem arising in the capital market called insider trading. Insider trading crime may be regarded as an economic crime. Insider trading can be done by the corporation, resulting from a corporate crime. Basically, liability regarding insider trading is shown by Article 104 of Act No. 8 of 1994 for which individuals or corporations are responsible. An imposition of jail and penalties come as the punishment of the lack of the responsibility. Due to the failure of imposing the imprisonment for corporations, the maximum fine penalty is given as the amount of Rp 15,000,000,000,00.